Acquisition of shares in a foreign country : substantive law and legal opinions : report of the Subcommittee on Legal Opinions of the Committee on Banking Law of the Section on Business Law of the International Bar Association and the Committee on Business Organisations of the Section on Business Law of the International Bar Association /: substantive law and legal opinions : report of the Subcommittee on Legal Opinions of the Committee on Banking Law of the Section on Business Law of the International Bar Association and the Committee on Business Organisations of the Section on Business Law of the International Bar Association. (1984) - Unknown
No abstract available